Pendidikan Literasi Berbasis Alquran dalam Tinjauan Teologis, Historis, dan Sosiologis - Thoriq Aziz Jayana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2021)
The Qur'an has brought the spirit of literacy since the beginning of Islam, from that spirit then made Muslims recorded in world history as people who have created a superior civilization that became the mecca of science. This paper seeks to describe more complexly the spirit of literacy in the Qur'an from various aspects ranging from theological, historical, and sociological reviews. The research method used is literature with content analysis through interpretation of meaning. This article is a discourse study to dig deeper into the literacy spirit that needs to be applied in Islamic society. As a result, there are many verses in the Qur'an that command literacy by mentioning literacy tools and inviting mankind to think deeply, seek knowledge, and make bookkeeping a tradition. The scope of literacy is very broad, starting from reading, observing, researching, understanding, analyzing, criticizing, and so on.